2022
DOI: 10.1039/d2cp00914e
|View full text |Cite
|
Sign up to set email alerts
|

Misconceptions about the chemistry of aqueous chlorine atoms and HClOH˙(aq), and a revised mechanism for the photochemical peroxydisulfate/chloride reaction

Abstract: It is widely considered that aqueous chlorine atoms (Cl•) convert to the species HClOH• with a half life of about 3 µs and that this species plays an important role...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 134 publications
0
3
0
Order By: Relevance
“…SO 4 •– oxidizes Cl – and gets converted via one-electron transfer (eq , k = 3.00 × 10 8 M –1 s –1 ) to Cl • , at a concentration of 7.05 × 10 –14 M under the experimental conditions (Table ). Cl • reacts with H 2 O (eq , k = 2.50 × 10 5 M –1 s –1 ) to form ClOH •– , ,, which subsequently decomposes and generates HO • (eq , k = 6.10 × 10 9 M –1 s –1 ). ,, The result suggests that Cl – at 20 mg L –1 promotes the degradation of micropollutants that preferably reacts with HO • or Cl • in the UV 222 /PDS AOP, while the degradation of micropollutants that preferably react with SO 4 •– (e.g., perfluorooctanoic acid) will be inhibited. Bromide (Br – ) was also detected in surface water in some countries (e.g., Israel and Australia), and the effect of Br – in the UV 222 /PDS AOP was investigated and discussed in Text S10. SO 4 + Cl SO 4 2 + Cl Cl + H 2 O ClOH + H + ClOH HO + Cl …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SO 4 •– oxidizes Cl – and gets converted via one-electron transfer (eq , k = 3.00 × 10 8 M –1 s –1 ) to Cl • , at a concentration of 7.05 × 10 –14 M under the experimental conditions (Table ). Cl • reacts with H 2 O (eq , k = 2.50 × 10 5 M –1 s –1 ) to form ClOH •– , ,, which subsequently decomposes and generates HO • (eq , k = 6.10 × 10 9 M –1 s –1 ). ,, The result suggests that Cl – at 20 mg L –1 promotes the degradation of micropollutants that preferably reacts with HO • or Cl • in the UV 222 /PDS AOP, while the degradation of micropollutants that preferably react with SO 4 •– (e.g., perfluorooctanoic acid) will be inhibited. Bromide (Br – ) was also detected in surface water in some countries (e.g., Israel and Australia), and the effect of Br – in the UV 222 /PDS AOP was investigated and discussed in Text S10. SO 4 + Cl SO 4 2 + Cl Cl + H 2 O ClOH + H + ClOH HO + Cl …”
Section: Resultsmentioning
confidence: 99%
“…Cl • reacts with H 2 O (eq 7, k = 2.50 × 10 5 M −1 s −1 ) to form ClOH •− , 8,49,50 which subsequently decomposes and generates HO • (eq 8, k = 6.10 × 10 9 M −1 s −1 ). 8,49,50 The result suggests that Cl − at 20 mg L −1 promotes the degradation of micropollutants that preferably reacts with HO micropollutants that preferably react with SO 4…”
Section: Effects Of Water Matrix Components On Radical Generation In ...mentioning
confidence: 96%
“…11 On a more fundamental side, there are important questions about the nature of the properties of simple atomic radicals in aqueous solution. For example, Stanbury 12 has examined the properties of Cl • in aqueous solutions to provide insights into the nature of the interactions of the Cl • with H 2 O and how best to interpret the results of a broad range of experiments using the principle of detailed balancing. He has shown that it is not appropriate to describe Cl • in H 2 O as a species distinct from HClOH • .…”
Section: ■ Introductionmentioning
confidence: 99%